Generalist practice with organizations and communities - Kirst-Ashman, Karen Kay (Cencage Learning, 2015)
Get a practical, comprehensive, and clearly written introduction to the fundamentals of macro practice with EMPOWERMENT SERIES: GENERALIST PRACTICE WITH ORGANIZATIONS AND COMMUNITIES, 6th Edition, which is thoroughly updated to reflect the Council on Social Work Education's (CSWE) latest ethical standards as well as contemporary issues in social work literature. The authors emphasize the practical skills needed for working successfully in macro practice--providing leadership, working with supervisors, managing conflict, working with the media, using new technological advances, fundraising, grant writing and managing stress. Learn how to build on one-on-one and group communication skills identified by the authors for community and organizational change. This edition's realistic vignettes and practical features--hands-on tips, sample forms, and a running case study--aim to deepen your expertise and enhance your performance in the field